Premiers résultats de l’exploration d’un site archéologique à Sillery - Gaumond, Michel (Cahiers de géographie du Québec, 1960)
Archeological investigation of an Indian site was conducted in 1959 and 1960 by /'Équipe d'archéologie de Québec at Sillery, within the limits of Metropolitan Québec. From written sources as well as from numerous documents found in situ, it appears that this site was the scène of much activity through the centuries. Artifacts were found, but no pottery, and this tends to suggest archaic occupation of a workshop-site. Most of the finds are attributed to the Montagnais, the Abenaquis, the Hurons and some other tribes. The dating of the material is uneasy for there is evidence of the removing of local topsoil and rocks for dock filling and house building purposes in the surroundings.